Interactions of PatA with the Divisome during Heterocyst Differentiation in Anabaena - Ana Valladares (American Society for Microbiology, 2020)
ABSTRACT The Anabaena organismic unit is a filament of communicating cells. Under conditions of nitrogen scarcity, some cells along the filament differentiate into heterocysts, which are specialized in the fixation of atmospheric N2 and provide the vegetative cells with N2 fixation products. At a certain stage, the differentiation process becomes irreversible, so that even when nitrogen is replenished, no return to the vegetative cell state takes place, possibly as a consequence of loss of cell division capacity. Upon N-stepdown, midcell FtsZ-rings were detected in vegetative cells, but not in differentiating cells, and this was also the case for ZipN, an essential protein that participates in FtsZ tethering to the cytoplasmic membrane and divisome organization. Later, expression of ftsZ was arrested in mature heterocysts. PatA is a protein required for the differentiation of intercalary heterocysts in Anabaena. The expression level of the patA gene was increased in differentiating cells, and a mutant strain lacking PatA exhibited enhanced FtsZ-rings. PatA was capable of direct interactions with ZipN and SepF, another essential component of the Anabaena Z-ring. Thus, PatA appears to promote inhibition of cell division in the differentiating cells, allowing progress of the differentiation process. PatA, which in mature heterocysts was detected at the cell poles, could interact also with SepJ, a protein involved in production of the septal junctions that provide cell-cell adhesion and intercellular communication in the filament, hinting at a further role of PatA in the formation or stability of the intercellular structures that are at the basis of the multicellular character of Anabaena. IMPORTANCE Anabaena is a cyanobacterial model that represents an ancient and simple form of biological multicellularity. The Anabaena organism is a filament of cohesive and communicating cells that can include cells specialized in different tasks. Thus, under conditions of nitrogen scarcity, certain cells of the filament differentiate into heterocysts, which fix atmospheric nitrogen and provide organic nitrogen to the rest of cells, which, in turn, provide heterocysts with organic carbon. Heterocyst differentiation involves extensive morphological, biochemical, and genetic changes, becoming irreversible at a certain stage. We studied the regulation during heterocyst differentiation of several essential components of the Anabaena cell division machinery and found that protein PatA, which is required for differentiation and is induced in differentiating cells, interacts with essential cell division factors and destabilizes the cell division complex. This suggests a mechanism for establishment of commitment to differentiation by inhibition of cell division.